2014
DOI: 10.1109/jphot.2014.2374596
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Carrier Injection Using Graded Superlattice Electron Blocking Layer for UVB Light-Emitting Diodes

Abstract: We have studied enhanced carrier injection by having an electron blocking layer (EBL) based on a graded superlattice (SL) design. Here, we examine, using a selfconsistent 6 Â 6 kÁp method, the energy band alignment diagrams under equilibrium and forward bias conditions while also considering carrier distribution and recombination rates (Shockley-Read-Hall, Auger, and radiative recombination rates). The graded SL is based on Al x Ga 1Àx N (larger bandgap) Al 0:5 Ga 0:5 N (smaller bandgap) SL, where x is changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…At high injection current levels, it is one of the main causes of efficiency rollover or droop in nitride-based devices. 46 However, the Auger recombination is abnormally lower compared to the radiative recombination rate in the n-polar TJ LED at an emission wavelength of 284 nm. These results suggested that the TJ-LED has a low Trap-Related Dislocation Density (TDD) because, in the TJ-LED, the Auger recombination is minimal in contrast to the radiative recombination rate.…”
Section: Resultsmentioning
confidence: 99%
“…At high injection current levels, it is one of the main causes of efficiency rollover or droop in nitride-based devices. 46 However, the Auger recombination is abnormally lower compared to the radiative recombination rate in the n-polar TJ LED at an emission wavelength of 284 nm. These results suggested that the TJ-LED has a low Trap-Related Dislocation Density (TDD) because, in the TJ-LED, the Auger recombination is minimal in contrast to the radiative recombination rate.…”
Section: Resultsmentioning
confidence: 99%
“…This is because that resonant tunneling of hole, which is a quantum mechanical process, through quantized resonant states generated in the superlattice system. 27,28 Besides, the additional advantage of the SPS structure can enhance the ionization efficiency of the dopants due to the polarization-induced reduction in the acceptor ionization energy. In other words, the hole density is mainly determined by the polarization-induced interface charges at the interface of GaN/InGaN SPS structure.…”
Section: Resultsmentioning
confidence: 99%
“…In similar scenarios, the term polarization-induced 'doping' has been widely used in the literature, which should be physically referred to as an increase in 'carrier' concentrations (not the dopant concentration). Further, a graded-AlGaN layer [76,[96][97][98][99] can assist the hole transport from the p-type cladding layer towards the active regions [100][101][102]. As shown in figures 5(a)-(c), hole transport can be facilitated by replacing the bulk AlGaN electron blocking layer (EBL) with a graded-AlGaN EBL or alternating AlN/AlGaN superlattice (SL) layers, thereby reducing the valence band offset or increasing the hole tunneling probability [96,97,103,104].…”
Section: Te-tm Polarization Issuesmentioning
confidence: 99%